دور المجتمع المدني في التنمية السياسية – دراسة حالة المجتمع المدني الجزائري 1989/2016 ــ - العابد, بالقاسم (جامعة الوادي -University eloued, 2017)
تناولت هذه الدراسة دور المجتمع المدني في التنمية السياسية في الجزائر من خلال الاطار الدستوري والقانوني خاصة في فترة التعددية السياسية، مع التركيز على أداء تلك المؤسسات ودورها في التنمية السياسية، وكذا معرفة واقع التنمية السياسية في الجزائر وما مدى فاعلية المجتمع المدني في ذلك ,وللوصول إلى هذا تم تحديد إطار نظري للدارسة تناول مفهوم المجتمع المدني والتنمية السياسية ، ثم الولوج إلى جوهر الموضوع في فصل ثاني وثالث تم من خلالهما التركيز على مدى مساهمة المجتمع المدني في عملية التنمية السياسية في الجزائر. ثم الكشف عن مختلف تنظيمات المجتمع المدني من أحزاب سياسية وتنظيمات نقابية مند إقرار التعددية السياسية سنة 1989 ،وقد صاحب هذا التحول السياسي جملة من التشريعات والإجراءات الرامية إلى توسيع مجال حركة المجتمع المدني ،يتضح دور المجتمع المدني في الأحزاب السياسية وبعض تنظيمات المجتمع المدني في التنمية السياسية في الجزائر من خلال دورها في المشاركة السياسية بتناول مشاركة الأحزاب في الانتخابات الرئاسية و السلطة التشريعية , ودورها في تحقيق الاستقرار السياسي ,وإجمالا لمسنا أن هناك نوع من المشاركة السياسية للمجتمع المدني في الجزائر في عملية التنمية السياسية من خلال المشاركة السياسية وتفعيل الاستقرار السياسي، ورغم محاولات الأحزاب السياسية في ذلك ، إلا أن هذه المشاركة كانت محدودة سواء في الانتخابات الرئاسية أو في نشاطها الوظيفي في البرلمان, كما أن تفعيل دور المجتمع المدني في التنمية السياسية يتطلب توفر مجموعة من الآليات التي يمكن أن تساهم في تحقيق ذلك مثل الآليات (السياسية والقانونية والثقافية والاجتماعية، والآليات الاقتصادية )This research has studies the role of civil society on the Political development in Algeria from the constitutional & organizational point of view, especially in the moment of multiparty system, foxing on the performance of companies and its function on the Political development as well as, to know the realty of Political development in Algeria, and the efficiency of the civil society. To reach this, we precise the theoretical context of the study, speaking about the definition of civil society and the Political development. We penetrate into the heard of the subject. In the second and thirdly chapter, we focus on the contribution of the civil society on the Political development process in Algeria. We have shown different organizations in the civil society such as: parties, syndicate institutions, since the multiparty system has been decided on 1989, this political change has been accompanied by several legislations, laws aiming to huge the movement of civil society. The role of the civil society in the political parties, and other organizations of the civil society on the Political development in Algeria through its function on the participation on political contribution by treating the participation of parties in Presidential Elections, and legislative power, also its role on the political sustainability and political process. Generally, we have noticed a kind of political participation of Algerian civil society on the Political development, and the efficiency of the political sustainability political process. In spite of that, the participation of Political parties is limited on the Presidential Elections, and on its functional role on the Parliament, the role of the civil society on the political development should have some mechanism in order to realize this process (Political, legal, cultural, social and economic).
ماستر حكم راشد
Keywords: المجتمع المدني، التنمية السياسية، الأحزاب السياسية، الجمعيات ، المشاركة السياسية، الاستقرار السياسي.; civil society, Political development, Political Participation, political sustainability